ChemInform Abstract: N‐Heterocyclic‐Carbene‐Catalyzed Sulfa‐Michael Additions. Issue 49 (December 2015) - Li, Yuan‐Zhen; Wang, Ying; Du, Guang‐Fen; Zhang, Hai‐Yan; Yang, Hong‐Li; He, Lin
Abstract: The mild procedure tolerates various functionalities in the unsaturated ketone substrates and affords the required β‐keto sulfides in generally high yields.